Fuzzy variable impedance control of space manipulator with unknown environmental stiffness identification - Pu, Yuxue; Zhao, Yibing; Zhang, Chongfeng; Zou, Huaiwu (Advanced robotics, 2025)
To accomplish interaction tasks in complex contact environments, space manipulators must rely on effective compliance control. However, in practical applications, the parameters of dynamic contact environment are difficult to be measured in real time, which brings great challenges to the implementation of compliance control. To address this issue, a variable impedance control method combining with online identification of environmental parameters is proposed. First, leveraging the error between predicted and measured contact forces, a dynamic forgetting factor adjustment strategy is designed, leading to the development of a Variable Forgetting Factor Recursive Least Squares (VFRLS) algorithm. This algorithm enables fast and high-precision online identification of stiffness parameters in unknown and time-varying contact environments. Second, to adapt to dynamically changing environmental parameters, a dynamic damping adjustment strategy is introduced. Building upon this, a Fuzzy Variable Impedance Control (FVIC) method is proposed, incorporating a hyperbolic tangent function and fuzzy logic for enhanced adaptability. Simulation results demonstrate that, compared to classical impedance control, the proposed FVIC-VFRLS control method achieves faster convergence and superior performance in suppressing force overshoot, proving its effectiveness in dynamic and uncertain environments.